Hyponym Games in Enriching Students’ English Vocabulary: A Case Study in Junior High School - Muhamad Sofian Hadi; Monica Lucy Widiyaningsih (Scope : Journal of English Language Teaching, 2021)
This study aimed to measure the effectiveness of Hyponym Games in improving the vocabulary mastery of 7th graders of SMP Muhammadiyah 01 Sukajaya. It was a quantitative study applying pre-experimental approach with one group of pre-test and post-test design. A total number of 30 students participated in this study. The results of t-test statistical data analysis revealed that in the pre-test, the average score gained by the students was 54, while in the post-test, the students obtained the average score of  74.73. Additionally, the calculation of the data showed that in the significance level of 0.05, tcalwas 7.0 with ttableof 1.701, or 7.0 > 1.701. Therefore, this study confirms that Hyponym Games are effective to enrich students’ vocabulary mastery.